Continuously Frequency-Tunable Horn Filtennas Based on Dual-Post Resonators - Andreia A. C. Alves; Luis G. da Silva; Evandro C. Vilas Boas; Danilo H. Spadoti; S. Arismar Cerqueira (International Journal of Antennas and Propagation)
This work reports the concept and development of two mechanically frequency-tunable horn filtennas for microwave and millimeter-waves. Our design approach relies on the integration of a horn antenna with a mechanically tunable filter based on dual-post resonators. The proposed filtennas have been manufactured and experimentally characterized, by means of reflection coefficient, radiation pattern, and gain. Measurements demonstrate that both filtennas have a tuning ratio of approximately 1.37 with continuous adjustment. The first prototype operates from 2.56 to 3.50 GHz, whereas in the second one the bandwidth is from 17.4 to 24.0 GHz. In addition, the higher-frequency filtenna has been implemented in a 5.0-meter-reach indoor environment, using a 16-QAM signal at 24 GHz. The best configuration in terms of performance resulted in a root mean square error vector magnitude (EVMRMS) and antenna radiation efficiency of 3.69% and 97.0%, respectively.